Let us make them listen: Review of the book 'If they let me speak' - Tanno, Ana Luiza; Ferreira, Marina; Weber, Victor M.; Castro Neves, Ana Paula de (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2021)
Book Review of Se me deixam falar, by Moema Viezzer, with the narratives taken by the author of Domitlia Barrios, a Bolivian union leader who fought for the rights of her people, especially women and the working class during the various coups and dictatorships in the history of Bolivia. In addition to being a miner's wife, the union member was also the daughter of a miner and lived for most of her life in a state-owned mining company called Siglo XX, where workers' conditions were unhealthy. The book divides Domitila's narrative into her life, her situation, and her claims, all narrated without changes in Domitila's idioms. The book shows part of Latin American struggle processes from a feminine perspective, almost never found in large historical narratives. It uses a very close past so that we can bring new perspectives of fight of the same struggles for all the Latin American future.
Keywords: unionism, mining, Latin American.